DISIPLIN PEGAWAI NEGERI SIPIL DI DINAS SOSIAL DAN PEMBERDAYAAN MASYARAKAT KOTA MANADO PROVINSI SULAWESI UTARA - yeti fatimah; Enrico Leonardus Tangkere; Yeti Rohayati (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
ABSTRACT Problem Statement/Background (GAP): Disciplinary violations such as tardiness, early departures, and unexcused absences remain frequent at the Social and Community Empowerment Office of Manado City, despite the enactment of Government Regulation No. 94 of 2021 concerning Civil Servant Discipline. Purpose: This study aims to examine of discipline among civil servants at the Social and Community Empowerment Office of Manado City, North Sulawesi Province. Method: This research employs a descriptive qualitative method with an inductive approach. Data were collected through observation, interviews, and documentation. The data analysis process includes data reduction, data presentation, and drawing conclusions, using a theoretical framework based on the three dimensions of discipline proposed by Sutrisno in Hamali (2018:214): behavior, rewards, and punishment. Result: The findings show that the implementation of discipline, when viewed through these three dimensions, generally aligns with existing regulations. However, violations persist due to internal factors such as personal habits and lack of awareness of regulations, as well as external factors such as fieldwork locations and insufficient supervision. Disciplinary enforcement is carried out through allowance deductions, persuasive approaches, and routine socialization led by the leadership. Conclusion: The study concludes that disciplinary enforcement must be consistent and continuous, supported by improved regulatory understanding and a work environment conducive to building a professional and disciplined work culture. Keywords: discipline, civil servants, violations.